Relationship between Frequency of Sugar Sweetened-Beverages (SSB) Consumption and Prediabetes: Aim For Screening Prediabetes Among Medical Students - Nasution, Huwainan Nisa; Febriyanti, Eka; Suryani, Des (Universitas Muhammadiyah Sumatera Utara, 2022)
Sugar sweetened-beverages (SSB) is not only found in soft drinks, fruit juice drinks, or energy drinks, but also various drinks that are currently